CAPS criteria fail to identify most severely-ill thrombotic antiphospholipid syndrome patients requiring intensive care unit admission. (September 2019) - Pineton de Chambrun, Marc; Larcher, Romaric; Pène, Frédéric; Argaud, Laurent; Demoule, Alexandre; Jamme, Matthieu; Coudroy, Remi; Mathian, Alexis; Gibelin, Aude; Azoulay, Elie; Tandjaoui-Lambiotte, Yacine; Dargent, Auguste; et al.
Abstract: Purpose: Catastrophic antiphospholipid syndrome (CAPS), the most severe manifestation of antiphospholipid syndrome (APS), is characterised by simultaneous thromboses in multiple organs. Diagnosing CAPS can be challenging but its early recognition and management is crucial for a favourable outcome. This study was undertaken to evaluate the frequencies, distributions and ability to predict mortality of "definite/probable" or "no-CAPS" categories of thrombotic APS patients requiring admission to the intensive care unit (ICU). Methods: This French national multicentre retrospective study, conducted from January 2000 to September 2018, included all APS patients with any new thrombotic manifestation(s) admitted to 24 ICUs. Results: One hundred and thirty-four patients (male/female ratio: 0.4; mean age at admission: 45.4 ± 15.0 years), who experienced 152 CAPS episodes, required ICU admission. The numbers of definite, probable or no-CAPS episodes, respectively, were: 11 (7.2%), 60 (39.5%) and 81 (53.3%). No histopathological proof of microvascular thrombosis was the most frequent reason for not being classified as definite CAPS. Overall, 35/152 (23.0%) episodes were fatal, with comparable rates for definite/probable CAPS and no CAPS (23% vs. 28.8% respectively, p = 0.4). The Kaplan–Meier curve of estimated probability of survival showed no between-group survival difference (log-rank test p = 0.5).Conclusions : In this study, CAPS criteria were not associated with mortality of thrombotic APS patients requiring ICU admission. Further studies are need evaluate the adequacy of CAPS criteria for critically-ill APS patients. Highlights: CAPS is the most severe APS manifestation. Distributions of CAPS criteria in critically-ill APS patients is unknown. Less than half of critically-ill APS patients have definite/probable CAPS. CAPS criteria failed to predict death of thrombotic APS patients in ICU admission.